The Effect Of Event Marketing On Purchase Decisions Through Purchase Interest In Tokopedia Marketplace (Case Study On Tokopedia Event Photocard Program) - Nuraeni, Laziani; Hadita (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study aims to analyze the effect of event marketing on purchase decisions through the purchase interest of the Tokopedia Marketplace at the Tokopedia photocard event. This study took 190 respondent who have participated in the Tokopedia photocard event. The sampling method in this research is using non-probability sampling method with purposive sampling technique. The analytical method used to test the hypothesis in this study is Structural Equation Modeling (SEM) through the SmartPLS 3.0 application. The results of this study indicate that event marketing has a positive and significant effect on purchase decision, event marketing has a positive and significant effect on purchase interest, purchase interest has a positive and significant effect on purchase decision, purchase interest can mediates the effect of event marketing on purchase decision.